NHERI@UTexas Experimental Facility With Large-Scale Mobile Shakers for Field Studies - Stokoe, Kenneth H.; Cox, Brady R.; Clayton, Patricia M.; Menq, Farnyuh (Frontiers in Built Environment, 2020)
The Natural Hazards Engineering Research Infrastructure (NHERI) experimental facility at the University of Texas (NHERI@UTexas) is funded by the National Science Foundation (NSF). NHERI@UTexas contributes unique, large-scale, hydraulically-controllable mobile shakers and associated instrumentation to study and develop novel, in-situ testing methods that can be used to evaluate the needs of existing infrastructure as well as optimize the design of future infrastructure. The ability to test existing infrastructure under actual field conditions bridges the gap in the transformative tools needed for the next frontier of resilient and sustainable natural-hazards research. Further, these unique facilities are available to any NSF-funded research. The field shakers and support equipment are described. Examples of on-going and future projects in three key areas of investigation that NHERI@UTexas is targeting are presented. These examples includes: (1) performing more accurate 2D/3D subsurface geotechnical imaging up larger depths, (2) characterizing liquefaction resistance and nonlinear dynamic behavior in situ soils, and (3) developing in-situ methods nondestructive soil-foundation-structure interaction (SFSI) studies.